Análisis y problemática de los espacios de montaña en España. - Navarro Madrid, Angel; Sabaté Martínez, Ana; Troitiño Vinuesa, Miguel Ángel; Ferreras Chasco, Casildo (Anales de Geografía de la Universidad Complutense, 1985)
Sin resumen